Antioxidant Activity Test of Combination Extract from Roselle Flower (Hibiscus sabdariffa L.) and Basil Leaf (Ocimum sanctum L.) in Vitro Using the DPPH Method - Muhammad Iqbal (Lembaga Pengembangan Kinerja Dosen, 2025)
Antioxidants are substances that can provide protection against endogenous and exogenous oxidative stress by capturing free radicals. Antioxidants are molecules that can inhibit the oxidation of other molecules. Antioxidants are generally phenolic or flavonoid compounds that are spread throughout the medicinal plant parts, including rosela and basil. Roselle petals contain anthocyanins that act as antioxidants by reducing free radicals that attack body molecules. Flavonoids from basil leaves have antioxidant effects by scavenging free radicals. This study aims to determine the antioxidant activity of a combination of rosela flower extract and basil leaf extract. The stages of the research method include 500 g of roselle flowers and basil leaves each extracted using 70% ethanol by maceration method and the combination of roselle flower extract and basil leaf extract was tested for antioxidant activity in vitro using 1,1-diphenyl-2-picrylhydrazine (DPPH) receptor. The results showed that the yield of roselle flower extract was 13.28% and basil leaf extract was 12.52%. The results of the in vitro antioxidant activity test showed that the combination of roselle flower and basil leaf extracts with a ratio of 1:1, 1:2, and 2:1 had strong antioxidant activity with IC50 values of 70.33 µg/ml, 56.92 µg/ml, and 57.90 µg/ml, respectively.